Steviol Glycosides and their use in food processing: A review - Mehrotra, Rolly; DHEER SINGH; AVINASH TIWARI (Innovare Journal of Food Sciences, 2014)
Steviol glycosides are the proteinacious secondary metabolites present in the leaves of Stevia rebaudiana Bertoni. These SG's are the principal sweetening agents which are 200-300 times more sweeter than sucrose. A number of SG's are present in the leaves of Stevia namely, stevioside, dulcoside A, rebaudioside A, rebaudioside B, rebaudioside C (previously known as dulcoside B), rebaudioside D, rebaudioside E and steviolbioside, 100–125. At the 63rd meeting a temporary ADI of 0-2 mg/kg bodyweight and day, expressed as steviol, was established based on a No-Observed-Effect-Level (NOEL). Steviol glycoside extracts have broad applications as sweetener in the manufacture of fruit and milk drinks, desserts, yoghurt, delicacies, confectioneries, fruit products, processed seafood products, pickles, table-top sweeteners and dietary supplements. Other aspects considered are physicochemical and biologic properties for food processing, stability and therapeutic value of SG's. nutritional information, Stevia market and household uses.